Paradoxical Roles of the MAL/Tirap Adaptor in Pathologies - Belhaouane, Imène; Hoffmann, Eik; Chamaillard, Mathias; Brodin, Priscille; Machelart, Arnaud (Frontiers in Immunology, 2020)
Toll-like receptors (TLRs) are at the forefront of pathogen recognition ensuring host fitness and eliciting protective cellular and humoral responses. Signaling pathways downstream of TLRs are tightly regulated for preventing collateral damage and loss of tolerance towards commensals. To trigger effective intracellular signaling, these receptors require the involvement of adaptor proteins. Among these, Toll/Interleukin-1 receptor domain containing adaptor protein (Tirap or MAL) plays an important role in establishing immune responses. Loss of function of MAL was associated with either disease susceptibility or resistance. These opposite effects reveal paradoxical functions of MAL and their importance in containing infectious or non-infectious diseases. In this review, we summarize the current knowledge on the signaling pathways involving MAL in different pathologies, their impact on inducing protective or non-protective responses and discuss the versatile features of MAL on the case of tuberculosis based on what we recently learned on immune escape strategies evolved by other pathogens.